2019
DOI: 10.1002/jca.21694
|View full text |Cite
|
Sign up to set email alerts
|

Excellent response to therapeutic plasma exchange in myasthenia gravis patients irrespective of antibody status

Abstract: Introduction The primary objective of this study was to assess response to plasma exchange (PLEX) in myasthenia gravis (MG) patients with and without autoantibodies (Ab) to acetylcholine receptor (AChR) or muscle‐specific kinase (MuSK). Analysis was also done to determine if correlation existed between sex, early or late onset MG, thymoma, or thymectomy and response to PLEX. Materials and Methods Data was analyzed on 58 consecutive MG patients treated with PLEX. Responses were categorized as complete response,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 26 publications
0
12
2
Order By: Relevance
“…Among the regimens not considered maintenance treatments, PLEX obtained the highest IT response rate; however, AZA and MMF showed the highest response and sustained response rates when all types of treatment were considered. A good response rate has been reported for PLEX in other immune‐mediated diseases involving autoantibodies, notably a response rate of 96% in myasthenia gravis, although it should be taken into account that the action mechanisms of PLEX are not limited to autoantibody removal alone . We highlight the excellent response of patients treated with AZA (5/5) and MMF (3/4), which were always administered in combination (AZA always with corticosteroids).…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Among the regimens not considered maintenance treatments, PLEX obtained the highest IT response rate; however, AZA and MMF showed the highest response and sustained response rates when all types of treatment were considered. A good response rate has been reported for PLEX in other immune‐mediated diseases involving autoantibodies, notably a response rate of 96% in myasthenia gravis, although it should be taken into account that the action mechanisms of PLEX are not limited to autoantibody removal alone . We highlight the excellent response of patients treated with AZA (5/5) and MMF (3/4), which were always administered in combination (AZA always with corticosteroids).…”
Section: Discussioncontrasting
confidence: 93%
“…30 Among the F I G U R E 2 Response to IT type are not limited to autoantibody removal alone. 31 We highlight the excellent response of patients treated with AZA (5/5) and MMF (3/4), which were always administered in combination (AZA always with corticosteroids).…”
Section: Discussionmentioning
confidence: 93%
“…Rajesh, K and Carandina‐Maffeis, R have have shown that plasma exchange might improve short‐term prognosis in patients with MG (Carandina‐Maffeis et al., 2004 ; Kumar et al., 2015 ), wherese, Newsom‐Davis, J reported that the AChR‐Ab concentration negatively correlates with muscle strength after plasma exchange (Newsom‐Davis et al., 1978 ). Usmani, A found that LOMG and male patients are more likely to have symptomatic relief after using plasma exchange, and antibody titers may be an effective way to monitor the plasma exchange response of patients with MG (Usmani et al., 2019 ). The two patients who received plasma exchange treatment in our study showed reduced AChR‐Ab concentration and improved clinical symptoms after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of severe relapses, with mainly bulbar symptomatology, and life-threatening myasthenic crisis are similar between MuSK- and AChR-MG. Acute administration of intravenous immunoglobulins (IVIg) and plasma exchange are both usually effective (for the latter up to 96% of positive response irrespective of patients’ antibody status) with rapid control of the symptoms which last for about 4–6 weeks (Usmani et al, 2019 ). Although considered equal in the treatment of myasthenia (Rønager et al, 2001 ), plasma exchange has been reported to be faster and more effective compared to IVIg in MuSK-MG patients (Guptill and Sanders, 2010 ; Pasnoor et al, 2010 ) and, therefore, should be prioritized.…”
Section: Treatment Of Musk-mgmentioning
confidence: 99%